Polar stratospheric clouds and the Antarctic ozone hole - Poole, Lamont R.; Mccormick, M. Patrick (1988)
A theoretical model for the formation and growth of polar stratospheric clouds (PSCs) has been developed. Results for the calculated temperature dependence of optical backscattering are found to agree well with values obtained during two Arctic airborne-lidar experiments. Results for PSC formation in Antarctica show that at the 70-mbar level, about 80 percent of the HNO3 and about 30 percent of the H2O vapor available may be sequestered in relatively large PSC particles at a temperature near 189 K.